The examination of the relationships among digital addiction, loneliness, shyness, and social anxiety in adolescents - Ime, Yakup; Akyıl, Yusuf; Çağlar, Azmi (Anales de Psicología / Annals of Psychology, 2024)
Digital addiction, which is determined as a common problem among adolescents in the last years, affects the lives of adolescents negatively in terms of many aspects. The aim of the study is to examine the relationships between adolescents' digital addiction, loneliness, shyness and social anxiety. Gate gathered from adolescents who completed Digital Addiction Scale, Short Form of UCLA Loneliness Scale, Shyness Scale, and DSM-5 Social Anxiety Disorder Severity Scale - Child Form. The suggested hypotheses have been tested using the data gathered from 991 adolescents and hierarchical regression analysis. The research findings found a positive and significant relationship between digital addiction, loneliness, shyness and social anxiety among adolescents. Furthermore, the findings show that digital addiction, loneliness, and shyness predict social anxiety. The results obtained prove that digital addiction, loneliness and shyness have an effect on social anxiety. According to the findings, it is suggested to apply various educational interventions by mental health professionals to adolescents who show signs of digital addiction, loneliness, shyness, and social anxiety.